Information and Communication Technologies and Employment: Complements or Substitutes? - Younchawou, Ngouwouo; Moumie, Eric Mouchili (Asian Journal of Empirical Research, 2022)
Information and communication technologies have changed the way in which a very large number of professions are exercised. As a result, digital technology can therefore contribute to the reduction or destruction of jobs and consequently to the rise in unemployment. Hence the fear of workers regarding the substitution of labor by machinery. Nevertheless, Schumpeterian theory maintains that technical progress generates opportunities for profit, and therefore investment opportunities, which when seized by companies are transformed into jobs. It is in the light of this controversy that the purpose of this paper is to analyze the effect of information and communication technologies on employment in Cameroon. By applying the OLS method to data covering the period 1980-2016, the results reveal that ICT promotes job creation in Cameroon. Thus, we suggest to the Cameroonian government to create more favorable conditions for the development of ICTs which will have the positive externality of job creation.